Interpersonal discussions and immigration attitudes - Kalogeropoulos, Antonis and Hopmann, David Nicolas (Communications, 2019)
Abstract The antecedents of immigration attitudes have been extensively examined in academic research, in particular, with respect to media use and personal contact with immigrants. Research on the role of interpersonal discussions about the issue of immigration has been scarce, however. Results from a two-wave panel survey show that individuals holding unfavorable attitudes towards immigration engaged more often in interpersonal communication about immigration, which colored the overall effect of engaging in such discussions. The implications of these results are discussed in the concluding section.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTUxNS9jb21tdW4tMjAxOC0yMDA3